Gastrointestinal parasites in Colombian sliders Trachemys callirostris (Emydidae) illegally trafficked in Córdoba, Colombia - Blanco Martínez, Rafael David (2021)
The presence of gastrointestinal parasites in gastrointestinal tract of 100 Colombian sliders (Trachemys callirostris) admitted to the Wildlife Care and Assessment Center (CAV), Córdoba, Colombia, during 2009 and 2010, as a result of confiscations from illegal trafficking of wild animals. The gastrointestinal tracts were separated, washed and its contents were removed to identify and quantify the parasites. A total of 1064 individuals of the taxa Nematophila argentinum (44%), Serpinema sp (44%) and Spiroxys sp (12%) were isolated. The observed prevalences were 70% for N. argentinum (Trematode), and 63 and 49% for Serpinema sp and Spiroxys sp (Nematode), respectively. The mean intensity was 6.7 for N. argentinum, 7.3 for Serpinema sp, and 3.2 for Spiroxys sp. N. argentinum was mainly found in the large intestine (40%); however, this is the first report of this parasite in the mouth, oesophagus and cloaca. Individuals of Serpinema sp were found mixed within the content of the digestive tract, especially in the small intestine (63%), whereas Spiroxys sp were located mainly in the stomach (64%). The lesions found were focused and without compromising the lives of turtles.